Analysis of Textual Meaning on Lyrics of Supporter’s Chant to Support Football Players in English Premier League - NUR ROCHMAN FATONI; RIYADI SANTOSA; Prof. Djatmika . (Master Program in Linguistics, Diponegoro University, 2020)
The spoken language phenomenon in social interaction, like in the sports discourse domain, is always exciting but rare to be discussed. This study focuses on the textual meaning of the supporting chants to support football players sung by supporters of the English Premier League (EPL), especially from the six biggest clubs (The Big Six). It is a qualitative descriptive study using content analysis. Within the Systemic Functional Linguistic approach, this study reveals textual meaning through the analysis of Theme and Rhyme consist of the Topical Theme; Unmarked Topical Theme, and Marked Topical Theme, Textual Theme, and Interpersonal Theme. The data are clauses taken from the football player supporting-chant lyrics from the supporters of the big six clubs. The analysis results are obtained through domain, taxonomy, componential and cultural themes analysis. Six chants are analyzed by textual meaning. Topical Theme analysis shows the development of a topic in the lyrics of supporting chants. Textual Theme indicates the connecting clause from the previous. Interpersonal Theme shows the interaction and transacting socially. These themes created a smooth information flow on the chant. Besides, it brought the meaning of these lyrics delivered well to the listener.